Negative Impacts of the Practices of Acadjas on the Aheme Lake in Benin - DEDJIHO, Achile; Alassane, Abdoukarim; Chouti, Waris; SAGBO, VIDJANNANGNI ETIENNE; Changotade, Odilon; MAMA, DAOUDA; BOUKARI, MOUSSA; Sohounhloue, Dominique C. K. (My University, 2014)
The objective of this study is to reveal the negative impacts of the practices of acadjas on the Aheme lake in Benin. Various material and methods were used for the measures of the physicochemical parameters such as: colorimetric HACH DR/890, the multiparameter WTW 340i and specific kits for the dosage of minerals. Also, the investigations were made with the resources by persons. It emerges from this study that the practices of acadjas asphyxiate and disturb the lake species. In fact, the concentrations in dissolved oxygen became very weak (1595 mg/L to 3740 mg/L), and the contents of nitrites (2, 25 mg/L to 14, 5 mg/L), suspension materials and turbidity are raised. The consequences both on the aquatic fauna and on the vegetation of the bank are worrying. The waterside populations are also threatened. Some actions in an attempt to regulate the practice of acadjas and promote reforestation of the lagoon bank need to be put in place.
Keywords: Acadjas; Negative Impacts; Aquatic Fauna; Aheme Lake; Benin